PENGGUNAAN MEDIA WAYANG KARTUN MELALUI MODEL PAIRED STORYTELLING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN - Farroh, Karimatul; Nugraha, Enung; Farhurohman, Oman (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
The study aims to determine the use of cartoon puppet media through a paired storytelling model to improve reading comprehension skills in class IV MIS Nurul Hasanah Sukaharja. The type of research used in this research is a class action research (CAR) model by Kemmis & Mc. Taggart was carried out in 2 cycles consisting of four stages, namely planning, implementation, observation, and reflection. The subjects in this study were the fourth-grade students of MIS Nurul Hasanah Sukaharja, totaling 24 students. The data collection techniques used were interviews, observations about teacher and student actions, and reading comprehension test data for students. The results of this study show that the use of cartoon puppet media through the paired storytelling model in class IV MIS Nurul Hasanah Sukaharja is carried out well and is categorized very well. Then the ability to read comprehension on fictional story material after using cartoon puppet media through paired storytelling model in class IV MIS Nurul Hasanah Sukaharja has increased. The results of reading comprehension ability in the first cycle of observation of student activities obtained a percentage value of 72.72% with quite good qualifications, in the second cycle it increased by obtaining a percentage value of 90.9% with very good qualifications, and reading comprehension skills increased. This can be seen in the results of the reading comprehension test assessment results from the pre-cycle, cycle I, and cycle II. The average result value in the pre-cycle is 59.58, the first cycle gets an average value of 64.16 and the second cycle gets an average value of 76.67. In addition, the results of the assessment of the percentage of students' reading comprehension mastery in the pre-cycle obtained a percentage value of 45.83%, the first cycle obtained a percentage value of 58.33%, and the second cycle obtained a percentage value of 100%.